Changes in Motivation and Burnout Indices in High-Performance Coaches Over the Course of a Competitive Season. Issue 1 (2nd January 2016) - Bentzen, Marte; Lemyre, Pierre-Nicolas; Kenttä, Göran
Abstract : Being subject to a great range of demands is believed to increase burnout propensity in high-performance coaches. This study is the first to explore whether the 4-step self-determination theory process model is a valuable framework to better understand the process influencing burnout and well-being in high-performance coaches ( N = 343, M = 40.33 years) throughout a competitive season. Findings indicated that coaches on average increased in burnout and decreased in well-being. Hypotheses were to a large extent supported: change in perceived environment → change in psychological need satisfaction → change in autonomous motivation → change in burnout and well-being.